THE EFFECT OF ADVERSITY QUOTIENT ON WORKFORCE AGILITY WITH PERCEIVED ORGANIZATIONAL SUPPORT AS A MEDIATION VARIABLE - Andriani, Andriani; Hardjo, Suryani; Patisina, Patisina (Pena Cendekia Insani, 2026)
This study aims to examine the effect of Adversity Quotient on Workforce Agility with Perceived Organizational Support as a mediating variable. The proposed hypothesis is that adversity quotient affects workforce agility in civil servants with perceived organizational support as a mediating variable. The population consists of 3,083 civil servants in the Pidie Jaya Regency government environment. The sample consisted of 253 civil servants, using cluster sampling technique. This study employed a quantitative method with three scales: workforce agility scale, adversity quotient scale, and perceived organizational support scale. In this study, each variable will be analysed or CFA (confirmatory factor analysis) will be conducted with a critical loading factor value of 0.7. The hypothesis testing was carried out using SmartPLS (Partial Least Square) version 3.0 software. The results indicate that (1) there is an effect of adversity quotient on perceived organizational support among civil servants, with a t-statistic value of 47.031 > 1.96 and a p-value of 0.000 < 0.05. (2) There is an effect of perceived organizational support on workforce agility among civil servants, with a t-statistic value of 20.249 > 1.96 and a p-value of 0.000 < 0.05. (3) There is an effect of adversity quotient on workforce agility among civil servants, with a t-statistic value of 43.291 > 1.96 and a p-value of 0.000 < 0.05. (4) There is an effect of adversity quotient on workforce agility among civil servants with perceived organizational support as a mediating variable, with a t-statistic value of 18.558 > 1.96 and a p-value of 0.000 < 0.05.